El empleo informal y la recaudación tributaria en la región Loreto periodo 2013 – 2022 - Diaz Chavez, Angela Malena (2024)
The present research study carried out carefully examined the relationship between labor informality and tax collection in the Loreto region during the period 2013-2022. The results revealed a significant positive correlation between informality and tax collection, supporting the general hypothesis of the research. In addition, critical factors were identified, such as tax culture and formalization costs, that influence this relationship. The conclusions highlight the importance of addressing informality in a comprehensive manner, promoting formalization and improving tax awareness to boost tax collection and economic development in the Loreto region. These findings have significant implications for public policy and offer a valuable contribution to the field of economics and taxation.